Use of Clonazepam and Avoidance of Sleep Deprivation in the Treatment of Juvenile Myoclonic Epilepsy - RAFIEI, S.M. (Iranian Journal of Child Neurology, 2009)
Objectives Juvenile Myoclonic Epilepsy(J.M.E.) needs life-long anti-epileptic drug (AED) treatment. Of various drugs tried in this condition, valproate effectively treats all types of seizures seen in J.M.E. Among valproate side effects, neural tube defects (NTD) in the offspring, is a deterring factor in its use in childbearing period. To avoid NTD, most authorities advise on switching to AED drug before conception.As well, the effects of valproate on male fertility is feared of. Clonazepam controls only the myoclonic jerks, leaving the patients unprotected and susceptible to generalized seizures, which mostly occur in the morning after sleep deprivation. Sleep deprivation is the most prevalent precipitating factor for generalized seizures in these patients. Materials &Methods Between Jan 2003 & April 2008, 15 newly diagnosed JME patients (9 girls, 6 boys), were given clonazepam (1.0-4.0 mg) at bedtime, and were compared to 16 patients on valproate treatment. All were advised to avoid sleep deprivation. Results This study showed, all patients in the clonazepam group, (100 %) had full control of their myoclonic jerks; 4(26.6%) had breakthrough episodes of generalized seizures, provoked by sleep deprivation; the rest (11,73.4 %), were in full remission of their myoclonic and generalized seizures. In control group, 2(12.5 %), had episodes of breakthrough, sleep-deprived, generalized seizures;the rest(14, 87.5%) were in remission. Statistically, there was no significance between the results in both groups. Clonazepam side effects were limited to mild to moderate drowsiness in the morning, eliminated by giving the dose earlier at night. Conclusion The study suggests that if J.M.E. patients avoid sleep deprivation, they can be reated with clonazepam alone to avoid side effects of valproate.